Building Entrepreneurial Intention: The Moderating Role of Social Support - Uce Karna Suganda; Eliana Donna Simbolon (PT Mattawang Mediatama Solution, 2023)
This study aims to examine individual internal and external factors that influence the intention to become an entrepreneur. This study looks at the influence of subjective norms and entrepreneurial passion on entrepreneurial intention, and considers the moderating role of social support in strengthening (or weakening) the relationship between these variables. Using the quantitative method, researchers conducted a survey of 300 students who are members of the Indonesian Young Student Association (HIPMI). The selection of this sample was carried out by purposive sampling method. The data obtained was processed using Structural Equation Modeling with AMOS. The results of this study indicate that subjective norms and entrepreneurial passion have a positive effect on entrepreneurial intention. In addition, this study also proves that social support moderates the effect of subjective norms and entrepreneurial passion on entrepreneurial intention. This research has implications if the intention to become an entrepreneur can grow from the individual and is driven by external aspects such as social support.